Strategic Fit Analysis: Using technology to reduce pre-harvest losses in sugar beets - Drye, Shelby (My University, 2019)
The Imperial Valley sugar beet industry suffers a revenue loss of 1.1 million dollars on average each year. This loss is due to the amount of sugar beet acres replanted as well as abandoned. Current methods of crop management are proving the need for more advanced technology that will allow producers and processors of sugar beets to recover lost revenue. This thesis was undertaken to study the use of ArcGIS, a new technology created for on-farm management, as a tool to reduce crop loss in sugar beet fields. The research not only found a revenue loss of 1.1 million dollars on average annually, but also the cause for the amount of sugar beet acres re-planted and abandoned, due, in part, to poor on-farm management of diseases. After interviewing growers, evaluating current farm technologies, and analyzing five-year production statistics, it is the recommendation of this study that ArcGIS would be best used to improve on-farm management decisions.
Keywords: Strategic Fit; Sugar Beets; ArcGIS; Economics; Imperial Valley